A High‐Performance Schottky Photodiode with Asymmetric Metal Contacts Constructed on 2D Bi2O2Se. (3rd February 2022) - Han, Jianfu; Fang, Chaocheng; Yu, Ming; Cao, Juexian; Huang, Kai
Abstract: Two‐dimensional Bi2 O2 Se is a newly developed 2D semiconductor material with air stability, moderate bandgap (0.8 eV), and high carrier mobility, which shows a bright prospect in optoelectronics. However, the reported photodetectors based on 2D Bi2 O2 Se suffer from the disadvantage of high dark current on account of the high carrier mobility and conductivity. Here, a Schottky photodiode based on 2D Bi2 O2 Se is constructed by employing an asymmetric electrodes technology. Due to the Schottky barrier, the dark current of the device is significantly suppressed. And the photodetector avoids the complex and precise preparation process of traditional heterojunction devices. The photodetector shows a broadband response from 450 to 1400 nm (Visible‐NIR), and the responsivity and detectivity reach 1.2 A W −1 and 7 × 10 11 Jones under the irradiation of 500 nm light (6.4 mW cm −2 ), respectively. Moreover, the device achieved On/Off ratios of more than three orders of magnitude and fast response at zero bias (117 ms for rise time and 58.5 ms for fall time). What's more, the responsivity reaches 193 A W −1, and the external quantum efficiency exceeds 47 899% with external bias (−0.5 V). These results indicate the unlimited potential of 2D Bi2 O2 Se in highly sensitive, broadband, and low‐power optoelectronics devices. Abstract : A Schottky photodiode is constructed by asymmetric contacts (Pd/Bi2 O2 Se/Ti). The device achieves excellent photoelectric performance at zero bias. Additionally, the responsivity of the photodetector reaches 193 A W −1, and the external quantum efficiency exceeds 47 899% with external bias voltage (−0.5 V). This work indicates the application prospect of Pd/Bi2 O2 Se/Ti photodetectors in ultra‐sensitive and low‐power optoelectronic devices.